A Review on Risk Management Framework for large scale scrum - Khurana, Simran Kaur; Wassay, Md Abdul; Verma, Karunendra (2022 International Conference on Computational Modelling, Simulation and Optimization (ICCMSO), 2022)
Risk management is a crucial part of every project. The primary objective of risk management is to recognize risks at an initial stage of the project and to take necessary steps to mitigate them. The effective prioritization of risk that come up is crucial and plays an important role in the field of software development. Using agile development techniques one of the main goals is to lower risk, which leads to more successful and efficient information systems. In order to produce high quality comparatively in a shorter span of time organizations are adopting agile approaches in distributed software development. In the recent times a lot of software based projects got converted into DAD projects. The primary advantages of these projects are saving the cost and proximity to market because they are spread over a large-scale scrum, Large scale scrum project development presents unique challenges in the risk management specially the difficulties faced in collaboration of teams where there is not a particular procedure to communicate and cooperate. Collaboration of teams and exchange of important information is an essential resource for the success of large scrum teams. Therefore it is important to create a dynamic method that encourages the communication and collaboration of team in large scale scrum environment. So in this paper we are going to review a framework for risk management in large scale scrum using outer meta data requests. This framework tries to manage the requests amongst different teams. As a result, it resists the missing collaboration of teams, threats and risks to the completion of projects. It also facilitates in the exchange of team knowledge, experience and skills. The proposed methodology was applied to two different case studies. The implementation and evaluation demonstrated the viability of proposed framework.